Intravenous Immunoglobulin G Suppresses Heat Shock Protein (HSP)-70 Expression and Enhances the Activity of HSP90 and Proteasome Inhibitors - Jones, Richard J.; Singh, Ram K.; Shirazi, Fazal; Wan, Jie; Wang, Hua; Wang, Xiaobin; Ha, Min Jin; Baljevic, Muhamed; Kuiatse, Isere; Davis, Richard E.; Orlowski, Robert Z. (Frontiers in Immunology, 2020)
Intravenous immunoglobulin G (IVIgG) is approved for primary immunodeficiency syndromes but may induce anti-cancer effects, and while this has been attributed to its anti-inflammatory properties, IgG against specific tumor targets may play a role. We evaluated IVIgG alone, and with a Heat shock protein (HSP)-90 or proteasome inhibitor, using multiple myeloma and mantle cell lymphoma (MCL) cells in vitro, and with the proteasome inhibitor bortezomib in vivo. IVIgG inhibited the growth of all cell lines tested, induced G1 cell cycle arrest, and suppressed pro-tumor cytokines including Interleukin (IL)-6, IL-8, and IL-10. Genomic and proteomic studies showed that IVIgG reduced tumor cell HSP70-1 levels by suppressing the ability of extracellular HSP70-1 to stimulate endogenous HSP70-1 promoter activity, and reduced extracellular vesicle uptake. Preparations of IVIgG were found to contain high titers of anti-HSP70-1 IgG, and recombinant HSP70-1 reduced the efficacy of IVIgG to suppress HSP70-1 levels. Combining IVIgG with the HSP90 inhibitor AUY922 produced superior cell growth inhibition and correlated with HSP70-1 suppression. Also, IVIgG with bortezomib or carfilzomib was superior to each single agent, and enhanced bortezomib's activity in bortezomib-resistant myeloma cells. Moreover, IVIgG reduced transfer of extracellular vesicles (EVs) to cells, and blocked transfer of bortezomib resistance through EVs. Finally, IVIgG with bortezomib were superior to the single agents in an in vivo myeloma model. These studies support the possibility that anti-HSP70-1 IgG contained in IVIgG can inhibit myeloma and MCL growth by interfering with a novel mechanism involving uptake of exogenous HSP70-1 which then induces its own promoter.